2002
DOI: 10.1046/j.1526-4610.2002.02173.x
|View full text |Cite
|
Sign up to set email alerts
|

Migraine and Coronary Heart Disease in Women and Men

Abstract: These prospective data suggest that migraine is not associated with increased risk of subsequent CHD events in women or men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
60
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 46 publications
8
60
0
Order By: Relevance
“…Those hallmarks of BP and serum lipid levels were in the similar results to female migraineurs in the present study. In contrast, the Physicians' Health Study of North America suggested no significant linkages of CVD risk factors between male migraineurs and controls [23]. The AGES-Reykjavik long-term study of Iceland exhibited no significant elevation of BP and serum TC levels in midlife MA and MO sufferers.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Those hallmarks of BP and serum lipid levels were in the similar results to female migraineurs in the present study. In contrast, the Physicians' Health Study of North America suggested no significant linkages of CVD risk factors between male migraineurs and controls [23]. The AGES-Reykjavik long-term study of Iceland exhibited no significant elevation of BP and serum TC levels in midlife MA and MO sufferers.…”
Section: Discussionmentioning
confidence: 85%
“…Causative mechanism of those vascular disorders might contribute to prothrombotic actions, CVD risk factors, vascular reactivity, specific gene variants, congenital heart diseases, migraine attack frequency, migrainespecific treatment and pathophysiological involvements of the migraine [5,9,[14][15][16]. Major prospective studies evaluated CVD risk factors in large number of migraineurs and non-migraineurs [10,13,17,23]. The Genetic Epidemiology of Migraine study of Netherlands pointed out that MA sufferer increased the frequency of hypercholesterolemia, hypertension, and prior history of early onset CVD and stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity and diabetes are metabolic disorders which also have a complex association with migraine. Although some clinical and population-based studies demonstrated a lower migraine prevalence in patients with diabetes mellitus [4,5], a similar [6] or higher prevalence [7,8] was found in other studies. The underlying mechanism of these comorbidities is still unknown.…”
Section: Introductionmentioning
confidence: 53%
“…In the ARCS, which enrolled 12,887 participants of both sexes, migraine patients were found to more frequently future science group future science group www.futuremedicine.com report chest pain or to have a history of angina, whereas the rates of myocardial infarction were similar in migraineurs and nonmigraineurs [35]. Similar results were obtained in the California Kaiser Permanence Care Programs, in which higher odds of angina or chest pain, but not myocardial infarction, were documented [36]. The higher incidence of chest pain had previously been attributed to a lower pain threshold in migraineurs, but more recent results seem to suggest a different interpretation.…”
Section: Association Between Migraine and Cardiovascular Diseasesmentioning
confidence: 78%